The Spectrum of Gastroenteritis at the Pediatric Outpatient Clinic,. Department of Child Health, School of Medicine, University of North Sumatera in 1982 - Taheng Sebayang; Atan Baas Sinuhaji; Tyahaya Bangun; Manihar D. Marbun; A. H. Sutanto (Indonesian Pediatric Society, 1988)
The number of children attending the Pediatric Outpatient Clinic of Pirngadi Hospital, Medan, during 1982 was 15.375. Out of these, 1246 (8.1%) had gastroenteritis. Most of the patients (1046 or 83.94%) were under two years old. The male to female ratio was 1.6: I. The peak incidence for allendance was in January, April, and May. Of 1057 patients under five years old, 383 (36.2%) also had malnutrition. The highest percentage (70. 75%) of those who had malnutrition was found in the I to 2 years age group. Of 370 patients whose Hb level was examined, 185 (50%) had anemia. The highest percentage (67.02%) was in the below 1 year group. Only 360 (28.8%) of gastroenteritis cases received oral rehydration solution. There were 23 (1.85%) cases in which diarrhea lasted longer than 7 days. The number of patients admitted to the ward was 213 (17.07%), and the highest percentage was in the above 3 years age group. The largest number of hospitalized patients was in January (43), February (21), and April (28); while the highest percentage was in April (20.40%), June (21.42%) and August (31.42%). Peak rainfall in Medan during 1982 was in October, November, and December, i.e. much 322.2 mmm, 366.4 and 382 mm, respectively.